2013
DOI: 10.7863/jum.2013.32.5.847
|View full text |Cite
|
Sign up to set email alerts
|

Does the Use of Automated Fetal Biometry Improve Clinical Work Flow Efficiency?

Abstract: This study was designed to compare the work flow efficiency of manual measurements of 5 fetal parameters with a novel technique that automatically measures these parameters from 2‐dimensional sonograms. This prospective study included 200 singleton pregnancies between 15 and 40 weeks' gestation. Patients were randomly allocated to either manual (n = 100) or automatic (n = 100) fetal biometry. The automatic measurement was performed using a commercially available software application. A digital video recorder c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…Espinoza et al . demonstrated that automated measurements reduced the number of steps used and time required to scan and could improve efficiency in workflow. The extra time could be used in communicating with the expectant mother, which could lead to a more positive experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Espinoza et al . demonstrated that automated measurements reduced the number of steps used and time required to scan and could improve efficiency in workflow. The extra time could be used in communicating with the expectant mother, which could lead to a more positive experience.…”
Section: Discussionmentioning
confidence: 99%
“…Rahmatullah et al 9 , using semi-automated measurement of the femur after segmentation and extraction, and Zalud et al 10 , using a different algorithm, also showed that automated measurements were reliable and reproducible. Espinoza et al demonstrated that automated measurements reduced the number of steps used and time required to scan and could improve efficiency in workflow 4 . The extra time could be used in communicating with the expectant mother, which could lead to a more positive experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these factors are operator-dependent and time-consuming involving multiple keystrokes and probe motions. Hence, to improve the workflows and reduce user variability in data acquisition, there has been an increasing demand for automatic estimation of fetal biometric parameters [3], [4].…”
Section: Introductionmentioning
confidence: 99%
“…To ensure a precise AC plane that is perpendicular to the true fetal longitudinal axis, clinician has to continuously move the transducer to find a plane consisting accurate landmarks. This process is firstly, cumbersome as fetal movement, breathing movement, and fetal position hinder prompt acquisition of the plane; and secondly, may lead to inaccurate measurement as inexperienced operators often fail to adhere to multiple landmarks of correct AC plane [6]. Therefore, development and implementation of automated fetal biometric measurements has recently gained spotlight in hope to improve clinicians' workflow and to overcome operator-dependency [1], [6].…”
Section: Introductionmentioning
confidence: 99%